Kewenangan Penyidik Kepolisian dalam Melakukan Penyidikan Tindak Pidana Korupsi - I Putu Edi Rusmana; I Made Minggu Widyantara; Luh Putu Suryani (Warmadewa Press, 2021)
Various laws and regulations that were created as a substitute for the previous rules, have not guaranteed success in eradicating corruption in Indonesia. The existence of several laws that regulate the authority and obligations of each law enforcement officer such as the Police, Prosecutors, Judges and the KPK so that it creates a blurring of their authority or there is an overlap of authority granted by the state creates a wrong perception, for example, the police as investigators feel they are authorized to carry out criminal investigations. corruption in addition to prosecutors and the KPK. The purpose of this study is to analyze the regulation of the authority of police investigators in conducting investigations into cases of criminal acts of corruption and what obstacles are faced by police investigators in conducting investigations into criminal acts of corruption. This research is a normative legal research type with a conceptual approach and a statutory approach. The legal sources used are secondary legal materials. The method of collecting legal material sources used in this study is the categorization of legal material sources. The legal materials that have been collected, then during the discussion will be processed and analyzed with legal interpretations and legal arguments, deductively then poured descriptively. The results of the study indicate that there is no cooperation in the form of legislation between police investigators and other law enforcement parties such as the Prosecutor's Office and the KPK, it is necessary to immediately establish a law that regulates clearly and in detail about the authority, cooperation and coordination in conducting criminal investigations. corruption, this needs to be done in order to be more effective and can be realized.